Wellness perceptions of female and male athletes playing in different volleyball leagues - GÜLER, MELİKE LALE (My University, 2023)
The purpose of this study was to compare the wellness self-perception of female and male volleyball players playing in different leagues according to league and gender. 78 women and 48 men aged 18-60 playing in different leagues of the Volleyball Federation of Turkey (Misli.com Sultans League (Super League – female), AXA Sigorta Efeler League (Super League – male), First League (female and male)) and independent of federation the Veteran’s League participated in the study voluntarily. An online survey was conducted with the volleyball players assessing their wellness self-perception and demographic characteristics. IBM SPSS Statistics 24.0 was used for data analysis. A t-test was used for independent groups and an ANOVA analysis for multiple comparisons. The level of statistical significance was set at p< 0.05. The results indicated that the perception of wellness for the volleyball players participating in the study was at a “high level”. It was determined that the scores of the participants’ wellness self-perception and sub-dimensions did not differ significantly by gender (p> 0.05). In addition, emotional wellness scores differ significantly according to the league they play (p< 0.05); however, it was determined that gender and league had no common effect on sub-dimensions and wellness self-perception total scores (p> 0.05).

Bu çalışmanın amacı, farklı liglerde oynayan kadın ve erkek voleybolcuların lig ve cinsiyete göre iyi yaşam benlik algılarını karşılaştırmaktır. Araştırmaya Türkiye Voleybol Federasyonu’nun farklı liglerinde (Misli.com Sultanlar Ligi (Süper Lig – kadın), AXA Sigorta Efeler Ligi (Süper Lig – erkek)), Birinci Lig (kadın ve erkek) ve federasyondan bağımsız olan Veteranlar Liginde oynayan 18-60 yaş arası 78 kadın ve 48 erkek gönüllü olarak katıldı. Voleybolcuların kendi sağlık algılarını ve demografik özelliklerini değerlendiren çevrimiçi bir anket yapıldı. Veri analizi için IBM SPSS Statistics 24.0 kullanıldı. Bağımsız gruplar için t-test ve çoklu karşılaştırmalar için ANOVA analizi kullanıldı. Anlamlılık düzeyi p<0.05 olarak kabul edildi. Sonuç olarak, araştırmaya katılan voleybolcuların iyilik algısının “yüksek düzeyde” olduğu bulundu. Katılımcıların iyilik hali benlik algısı ve alt boyut puanlarının cinsiyete göre anlamlı bir şekilde farklılaşmadığı belirlendi (p> 0.05). Voleybolcuların duygusal iyilik hali puanlarının oynadıkları lige göre istatistiksel olarak anlamlı farklılık tespit edildi (p< 0.05). Fakat cinsiyet ve ligin alt boyutlar ve iyilik hali toplam puanları üzerinde ortak etkisinin olmadığı belirlendi (p> 0.05).
Farklı liglerde oynayan kadın ve erkek voleybolcuların iyilik hali düzeylerinin karşılaştırılması
Keywords: Voleyball Players; Wellness Perceptions; Leagues; Voleybol Oyuncuları; İyilik Hali; Ligler